What counts in the immunological synapse? - Dustin, M (Cell Press, 2014)
Molecular interactions at the interface between helper T cells and antigen-presenting B cells govern the ability to produce specific antibodies, which is a central event in protective immunity generated by natural infection or man-made vaccines. In order for a T cell to deliver effective help to a B cell and guide affinity maturation, it needs to provide feedback that is proportional to the amount of antigen the B cell collects with its surface antibody. This review focuses on mechanisms by which T and B cells manage to count the products of antigen capture and encourage B cells with the best receptors to dominate the response and make antibody-producing plasma cells. We discuss what is known about the proportionality of T cells responses to presented antigens and consider the mechanisms that B cells may use to keep count of positive feedback from T cells.